A retrospective study of trifluridine/tipiracil in pretreated metastatic colorectal cancer patients in clinical practice. (9th March 2018) - Borelli, Beatrice; Zucchelli, Gemma; Rossini, Daniele; Cremolini, Chiara; Antoniotti, Carlotta; Moretto, Roberto; Marmorino, Federica; Colombo, Camilla; Vannini, Francesca; Delliponti, Laura; Spione, Mario; Ongaro, Elena; et al.
Aim: RECOURSE trial has shown a benefit for trifluridine/tipiracil (also known as TAS-102) over placebo in chemorefractory metastatic colorectal cancer (mCRC) patients. We evaluated efficacy and safety of patients treated with trifluridine/tipiracil in compassionate use.Patients & methods: RETROTAS is a retrospective study designed to evaluate efficacy and safety of trifluridine/tipiracil in mCRC patients previously exposed or not a candidate to all available drugs.Results: A total of 85 mCRC patients were included. Our data showed that 37.6% of patients achieved disease control. Median progression-free survival was 2.3 months; at 16 months follow-up, median overall survival was 9.2 months.Conclusion: This real-life experience confirms the safety and efficacy of trifluridine/tipiracil, resulting as a valid option in chemorefractory mCRC treatment scenario.